Addressing the situation of Roma in Slovakia in 1989--2020 through the idea of a comprehensive approach and Romani participation in its development and definition - Mušinka, Alexander (Romano džaniben, 2024)
The study analyzes the activities of Roma in Slovakia since the second half of the 1990s with the emphasis on the efforts of the Roma to move from the position of implementers of government policies and to start actively creating these policies and taking responsibility for them at the highest state level. A significant milestone in this process was the establishment of the Office of the Government Plenipotentiary for Roma Communities in 1999, which has been headed predominantly by Romani representatives since its inception. By 2020at least two efforts to develop the philosophy of a comprehensive approach took place on the grounds of the Office, under the management of the Roma themselves. None of them was ultimately implemented in Slovakia in the proposed form.
Keywords: Plenipotentiary for Roma communities; Government of the Slovak Republic; Roma participation; comprehensive approach